2023
DOI: 10.3390/biology12030485
|View full text |Cite
|
Sign up to set email alerts
|

Editorial to the Special Issue “Eco-Physiological and Molecular Basis of Stress Tolerance in Plants”

Abstract: Farmers are currently facing the challenge of producing sufficient crop yield [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…For instance, under PS MP stress a higher activation of GR and DHAR was observed only in roots, while only DHAR activity was increased in leaves, indicating the tissue specificity of the activation of the AsA-GSH cycle to encounter PS MP stress-induced oxidative stress (Li et al, 2021c). Likewise, Wang et al (2023) showed that the activities of CAT, GR, and SOD increased in roots until day 6 of the application of MP stress, then tended to decline until day 12 after MP stress, and increased again on day 18. Whereas in leaves, the activities of SOD, GR, and APX were continuously increased from day 6 to day 18 in an MP dosedependent manner.…”
Section: Tissue Specificity Of Antioxidant Productionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, under PS MP stress a higher activation of GR and DHAR was observed only in roots, while only DHAR activity was increased in leaves, indicating the tissue specificity of the activation of the AsA-GSH cycle to encounter PS MP stress-induced oxidative stress (Li et al, 2021c). Likewise, Wang et al (2023) showed that the activities of CAT, GR, and SOD increased in roots until day 6 of the application of MP stress, then tended to decline until day 12 after MP stress, and increased again on day 18. Whereas in leaves, the activities of SOD, GR, and APX were continuously increased from day 6 to day 18 in an MP dosedependent manner.…”
Section: Tissue Specificity Of Antioxidant Productionmentioning
confidence: 97%
“…Seed germination is the first phase in plant growth and is highly sensitive to stress conditions ( Wang and Tanveer, 2023 ) including MP stress ( Table 2 ). MP stress reduces seed germination by clogging the pores in the seed capsule ( Bosker et al., 2019 ), thus reducing water uptake and the imbibition process.…”
Section: Microplastic Effects On Plant Growthmentioning
confidence: 99%